Hubungan Kebiasaan Konsumsi Kopi dengan Tekanan Darah pada Lansia Riwayat Hipertensi - fika Sari; Reni Zulfitri; Nopriadi (Jurnal Vokasi Keperawatan (JVK), 2022)
Breast care aims to improve blood circulation and prevent blockage of the milk ducts so that breast milk is released. One of the breast treatments that can increase milk production is to do lactation massage, the types of lactation massage include oketani massage and oxytocin massage. In 1991, a midwife from Japan named Sotomi Oketani created a massage technique to overcome breastfeeding problems called oketani massage. Oxytocin massage itself is a massage along the spine which is one solution to overcome the non-smooth milk production. This study aims to determine the relationship between coffee consumption habits and blood pressure in the elderly with hypertension. This study uses a descriptive correlation research design with a cross-sectional approach, obtained a sample using purposive sampling technique of 96 people. The measuring instrument uses a coffee consumption habit questionnaire and a blood pressure check sheet.The majority of respondents aged 60-69 years as many as 82 people (85.4%) are in the elderly category. Gender is more male respondents, namely 61 respondents (63.5%). The most coffee consumption in the bad category ≥250 with the number of respondents being 49 respondents (51,4). The average blood pressure was 140/90 mmHg, namely 74 respondents (77.1). The results of statistical tests using the Chi-square test obtained p-value = 0.000 (<0.05) Ho are rejected, meaning that there is a significant relationship between coffee consumption habits and blood pressure in the elderly with a history of hypertension. There is a relationship between coffee consumption habits and blood pressure in the elderly with a history of hypertension. Future researchers are expected to be able to develop research with experimental methods to overcome the problem of hypertension in the elderly